2000
DOI: 10.1111/j.1553-2712.2000.tb01268.x
|View full text |Cite
|
Sign up to set email alerts
|

Low Plasma Thiamine Levels in Elder Patients Admitted through the Emergency Department

Abstract: Abstract. Objectives:To determine the prevalence of thiamine deficiency in a high-risk group of elder emergency department (ED) patients who reside in nursing homes and need admission to the hospital, and to determine the effect of patients' diets on this prevalence. Methods: This was an observational pilot study of 75 consecutive ED patients aged 65 years or older who lived in a nursing home and were admitted to the hospital. Plasma thiamine levels were measured by high-pressure liquid chromatography on serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 26 publications
1
21
1
Order By: Relevance
“…A likely explanation would be that in a community setting for the elderly the co-morbidities are functional illnesses and thus less severe than in a nursing, full-time care or hospital setting. This is supported by an observational study be Lee et al [75] who found a 14% prevalence of TD in elderly patients admitted to hospital from a nursing facility. This highlights that the predisposition to reduced TPP levels in the elderly increases the risk of TD in critical care scenarios.…”
Section: Post-analyticalsupporting
confidence: 68%
See 1 more Smart Citation
“…A likely explanation would be that in a community setting for the elderly the co-morbidities are functional illnesses and thus less severe than in a nursing, full-time care or hospital setting. This is supported by an observational study be Lee et al [75] who found a 14% prevalence of TD in elderly patients admitted to hospital from a nursing facility. This highlights that the predisposition to reduced TPP levels in the elderly increases the risk of TD in critical care scenarios.…”
Section: Post-analyticalsupporting
confidence: 68%
“…Studies of low thiamine compound levels include association with oxidative stress, sepsis, metabolic acidosis, cardiac failure, and neurodegeneration [16,62,[72][73][74]. The prevalence of TD in the ICU, hospitals and the elderly (>76 years of age) has also been examined [15,75,76]. A retrospective study by Cruickshank et al [63] observed a 20% prevalence of TD in intensive care patients requiring nutritional support.…”
Section: Pathophysiology Related To Tdmentioning
confidence: 99%
“…The acute neuropsychiatric consequence of thiamine (vitamin B1) deficiency, Wernicke’s encephalopathy (WE), is associated with conditions such as alcoholism, bariatric surgery for morbid obesity (Berger and Singhal, 2014; Merola et al, 2012), cancer, HIV/AIDS, and advanced age (Lee et al, 2000). Animal models support a contribution of classical sterile neuroinflammatory mechanisms (cf., Graeber et al, 2011) in thiamine deficiency related pathology.…”
Section: Introductionmentioning
confidence: 99%
“…The thiamine is absorbed by the small intestine, observed in the skeletal muscles, liver, heart, kidneys and brain with a high concentration, and a continuous supply is required with the limited storage in the tissues with half life of 10 to 20 days [52]. The plasma thiamine level for a healthy person is reported between 0.018 and 0.855μmol·mg-1 [53-55] and the thiamine level is within the normal range in the resting state of the subjects. Also, it is found that the thiamine level significantly increases for all treatment groups after 60 minutes of the exercise, metabolic requirement for glucose in the later part of the exercise and the thiamine concentration.…”
Section: Discussionmentioning
confidence: 99%